2019
DOI: 10.1002/smll.201903381
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophospholipids Increase Protocellular Stability to Metal Ions

Abstract: Model protocells have long been constructed with fatty acids, because these lipids are prebiotically plausible and can, at least theoretically, support a protocell life cycle. However, fatty acid protocells are stable only within a narrow range of pH and metal ion concentration. This instability is particularly problematic as the early Earth would have had a range of conditions, and extant life is completely reliant on metal ions for catalysis and the folding and activity of biological polymers. Here, prebioti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…In addition, prior work on an RNA aptamer found that encapsulation in fatty acid vesicles and POPC vesicles gave similar effects on RNA activity ( 34 ). Exploration of different vesicle compositions mimicking protocells, such as cyclic phospholipids ( 77 ), might be an avenue of future interest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior work on an RNA aptamer found that encapsulation in fatty acid vesicles and POPC vesicles gave similar effects on RNA activity ( 34 ). Exploration of different vesicle compositions mimicking protocells, such as cyclic phospholipids ( 77 ), might be an avenue of future interest.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, G3P can be produced from glycerol and is catalysed by a glycerol kinase (GK) in bacteria and eukarya, while archaea lacks GK. [21,65] To the best of our knowledge, there is no GK producing G1P. So far, the catalytic activity of one and the same enzyme producing both G1P and G3P from glycerol, if it existed, was not retained during the evolution.…”
Section: Scheme 3 Biosynthetic Pathways Leading To G3p (A) and G1p (mentioning
confidence: 99%
“…Several plausible prebiotic synthesis were explored, however all the proposed pathways, carried out in enzyme free conditions from glycerol (3) yield racemic phospholipids (6−8, Scheme 2-A) [50,52,[55][56][57][58][59] or racemic mixtures of glycerol phosphates (5a−c and 9−10, Scheme 2-B [34,[60][61][62][63][64]. In addition, the chemical imbalance between the R:S ratio of mono-and di-alky phosphates (6, 12 scheme 2-C) and cyclic glycerophosphates (cGP, 13, scheme 2-D) [65,66] from di-acyl glycerols 12 or glycerol 3, respectively, were not reported or investigated either. Remarkably, all the phospholipids crude mixtures containing 6−8, 12 and 13 are able, using appropriate buffers, to form giant vesicles that per sizes and membranes properties are similar to that of lipid bilayer of modern cells.…”
Section: Racemic Amphiphiles and Their Precursorsmentioning
confidence: 99%
“…Later, Duhan et al. in 2019 showed that indeed these cyclophospholipids increase the stability of fatty acid protocells [25] . Thus, phosphorylation by DAP of the three different classes of molecules, nucleosides, amino acids, and glycerol/fatty acids ‐under similar ambient conditions‐ led to their corresponding higher‐order structures, oligonucleotides, peptides, and protocells, respectively.…”
Section: Dap: Reactions With Organic Substratesmentioning
confidence: 99%